SISTEM MANAJEMEN PERSEDIAAN TERPADU UNTUK MENDUKUNG PENGEMBANGAN PRODUK UMKM PADA PARIWISATA BERKELANJUTAN DI DESA WISATA WATES JAYA, KABUPATEN BOGOR - Muliani, Lila; Suprayitno, Degdo; Hidayat, Yusup Rachmat (ITB AAS Indonesia Surakarta, 2024)
The issues faced by Small and Medium Enterprises (SMEs) in tourism villages, particularly regarding efficiency and effectiveness in the production process, remain an under-researched area. Most studies focus more on the development of tourism attractions and accommodations. However, within the 3S tourism concept (something to see, something to do, something to buy), the aspect of